Some Aspects in the PDE. The Dirichlet and the Cauchy Problems (Selecciones Matemáticas, 2024)
In this article we present two classic problems in PDE: the Dirichlet problem and the Cauchy problem. Some ideas are previously discussed, such as functions and identities’s Green, and “bad positions” problems. The work of L.Nirenberg [1] is discussed in  detail where some results of L.Hörmander [2] are used.
Keywords: Potential; Newton; Cuachy; Nirenberg; Hörmander; Problem and principle od Dirichlet; Cauchy problem